Contributing factors to the plasma albumin level at diagnosis of hematological malignancy. Issue 4 (7th August 2020) - Gradel, Kim Oren; Engberg, Henriette; Zampieri, Fernando G.; Póvoa, Pedro; Simonsen, Simone F.; Vinholt, Pernille Just; Garvik, Olav Sivertsen; Ljungdalh, Pernille S.; Frederiksen, Henrik
ABSTRACT: Objectives: Many factors contribute to the plasma albumin (PA) level. We aimed to quantify different factors' relative contribution to the PA level when diagnosing hematological malignancy (HM). Methods: The study was a population-based registry study including patients with HM in a Danish region. We applied multivariate linear regression analyses with C-reactive protein (CRP), WHO performance score (WHO-PS), age, sex, comorbidity, and HM type as exposures and the PA level on the day of the HM diagnosis (DX) as the outcome. The relative contribution of each exposure was determined as a percentage of the models' coefficient of determination (R 2 ). Results: In total, 2528 patients with HM had PA measured on DX. In the model comprising all exposures, CRP contributed with 65.8% to the R 2 of 0.389 whereas 3 variables (CRP, WHO-PS, HM type) together contributed with 96.1%. When CRP was excluded from the model, R 2 declined to 0.215 and the WHO-PS contributed with 96%. Other models, including separate analyses for each HM type, corroborated these results, except in myeloma patients where WHO-PS contributed with 61.1% to the R 2 of 0.234. Conclusion: The inflammation biomarker CRP was the main predictor of the PA level on DX. The WHO-PS also contributed to the PA level on DX whereas the remaining factors (HM type, age, sex, and comorbidity) were of much less importance.